Blue-grey pigmentation associated with levetiracetam use: a rare adverse effect - Yildirim, Harun; Cicek, Imren Nur; Arslan, Sumeyye; Yildirim, Ebru Aydin (Springer-Verlag Italia Srl, 2025)
[Abstract Not Available]